STOCK LIQUIDITY: THE ROLES OF FOREIGN AND LOCAL INSTITUTIONS - Ardan Ardiyanto; Ani Wilujeng Suryani; Ammar Bin Asbi (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2025)
High or low liquidity of stocks can affect investment decisions, liquid stocks tend to attract the attention of investors. One factor that can affect stock liquidity is institutional ownership. This study aims to determine the effect of foreign and local institutional ownership on stock liquidity. This research sample uses stock data on IDX and stock ownership data on KSEI in 2021. Stock liquidity data is calculated using the bid-ask spread. The hypothesis was tested using the quantile regression method. The results of this study indicate that foreign and local institutional ownership has a positive effect on stock liquidity. However, the coefficient value of foreign institutions is greater than that of local institutions, which means that foreign institutional ownership dominates in driving stock liquidity. These findings contribute theoretically to the validity of agency conflicts and some practically. First, these results can be used for investors in considering their investment decisions in stocks that have foreign and local institutional ownership structures. Second, these results can be used by management to consider the impact of the institutional ownership structure within the company.